Prosodic Orientation in English Conversation - Szczepek Reed, Beatrice. author. aut Link
XIV, 231 p.
Keywords: The first study, based on instances of everyday talk, to analyze prosodic orientation, a conversational strategy by which speakers design their speaking voice according to the vocal patterns used by their conversational partners. The book explores forms and functions of prosodic orientation, and offers a new perspective on prosody in conversation.